2021
DOI: 10.1016/j.jgo.2020.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of healthcare providers of older adults with cancer during the COVID-19 pandemic

Abstract: Objectives: Care for older adults with cancer became more challenging during the COVID-19 pandemic. We sought to examine healthcare providers' clinical barriers, patient questions, and overall experiences related to care delivery for these patients during the pandemic. Materials and methods: Members of the Advocacy Committee of the Cancer and Aging Research Group along with the Association of Community Cancer Centers developed a 20-question survey for healthcare providers of older adults with cancer. Eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 32 publications
(34 reference statements)
3
42
0
1
Order By: Relevance
“…Moreover, 15 (11.1%) studies included persons with specific conditions such as Alzheimer disease [ 33 - 35 ], Parkinson disease [ 36 ], frontotemporal lobar degeneration [ 37 ], severe cognitive impairments [ 38 ], ovarian cancer [ 39 ], gynecological cancer [ 40 ], patients with cancer actively treated with systemic therapy [ 41 ], pre-existing depression [ 42 ], chronic conditions [ 43 ], long-term respiratory conditions [ 44 ], migraine [ 45 ], epilepsy [ 46 ], and visual impairments [ 47 ]. A total of 29 (21.5%) studies were conducted in North America [ 40 , 42 , 43 , 48 - 73 ], 14 (10.3%) in China [ 46 , 74 - 86 ], 61 (45.1%) in Europe [ 33 - 38 , 41 , 44 , 87 - 139 ], 3 (2.2%) in Japan [ 140 - 142 ], 4 (3.0%) in Israel [ 143 - 146 ], 4 (3.0%) in Brazil [ 147 - 150 ], 4 (3.0%) in Australia [ 151 - 154 ], 2 (1.5%) in India [ 155 , 156 ], 1 (0.7%) in Malaysia [ 157 ], 2 (1.5%) in Kuwait [ 45 , 158 ], 1 (0.7%) in Saudi Arabia [ 159 ], 3 (2.2%) in Argentina [ 160 - 162 ], 1 (0.7%) in Cameroon [ 163 ], 1 (0.7%) in Russia [ 164 ], 1 (0.7%) in Ghana [ 47 ], 1 (0.7% in Cyprus [ 165 ], and 3 (2.2%) in multiple countries [ 39 , 166 , 167 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, 15 (11.1%) studies included persons with specific conditions such as Alzheimer disease [ 33 - 35 ], Parkinson disease [ 36 ], frontotemporal lobar degeneration [ 37 ], severe cognitive impairments [ 38 ], ovarian cancer [ 39 ], gynecological cancer [ 40 ], patients with cancer actively treated with systemic therapy [ 41 ], pre-existing depression [ 42 ], chronic conditions [ 43 ], long-term respiratory conditions [ 44 ], migraine [ 45 ], epilepsy [ 46 ], and visual impairments [ 47 ]. A total of 29 (21.5%) studies were conducted in North America [ 40 , 42 , 43 , 48 - 73 ], 14 (10.3%) in China [ 46 , 74 - 86 ], 61 (45.1%) in Europe [ 33 - 38 , 41 , 44 , 87 - 139 ], 3 (2.2%) in Japan [ 140 - 142 ], 4 (3.0%) in Israel [ 143 - 146 ], 4 (3.0%) in Brazil [ 147 - 150 ], 4 (3.0%) in Australia [ 151 - 154 ], 2 (1.5%) in India [ 155 , 156 ], 1 (0.7%) in Malaysia [ 157 ], 2 (1.5%) in Kuwait [ 45 , 158 ], 1 (0.7%) in Saudi Arabia [ 159 ], 3 (2.2%) in Argentina [ 160 - 162 ], 1 (0.7%) in Cameroon [ 163 ], 1 (0.7%) in Russia [ 164 ], 1 (0.7%) in Ghana [ 47 ], 1 (0.7% in Cyprus [ 165 ], and 3 (2.2%) in multiple countries [ 39 , 166 , 167 ].…”
Section: Resultsmentioning
confidence: 99%
“…Older adults reported unmet personal, domestic, or social needs [ 128 ]; difficulty finding help with functional needs such as bathing [ 62 ]; insufficient personal care [ 139 ]; decreased care rendered by caregivers [ 47 ]; and reductions in social support services hours [ 99 ]. Multiple barriers to care delivery were noted during this time [ 166 ]. For instance, one study reported that older adults were more likely to miss or cancel medical appointments [ 129 ], whereas another reported the opposite [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Greenberg, 2020) The main concerns of COVID-19 primary care providers are their patients' safety and treatment hindrances and their colleagues' mental health together with worries as regards their loved ones being infected. (Krok-Schoen et al, 2020) The COVID-19 contagion, mortality, and morbidity rates amplify the related psychological fear, leading to adverse mental health consequences. (Wong et al, 2020) Healthcare professionals ensure first-rate patient care and prevent infection outbreaks in hospitals throughout the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults reported unmet personal, domestic, or social needs [128]; difficulty finding help with functional needs such as bathing [62]; insufficient personal care [139]; decreased care rendered by caregivers [47]; and reductions in social support services hours [99]. Multiple barriers to care delivery were noted during this time [166]. For instance, one study reported that older adults were more likely to miss or cancel medical appointments [129], whereas another reported the opposite [60].…”
Section: Environmental Factorsmentioning
confidence: 99%